Exploring relationships between experience economy and satisfaction of visitors in rural tourism destination / Mazlina Mahdzar …[et al.] - Mahdzar, Mazlina; Saiful Raznan, Ainul Maisarah; Ahmad Jasmin, Norhafidzah; Abdul Aziz, Nur Afiqah (Universiti Teknologi MARA Shah Alam, 2020)
This study explores the visitors' experience on rural tourism destination in Tadom Hill Resorts, Selangor. The satisfactions were classified into Four Experience Economy which comprises of education experience, entertainment experience, esthetics experience, and escapism experience. The Four Experience Economy has become the foundation to the research frameworks. The study was conducted in Banting, Selangor, a destination that is known for its own charm on rural destinations. A total of 383 questionnaires were collected from the visitors that visits Tadom Hill Resorts and visitors that had experience from Tadom Hill Resorts visits. Correlation analysis are performed to test the relationship between the variables. Based on the results, there is a positive relationship between the four realms of experience economy and visitors' satisfaction. The findings of this study prove that it is crucial to assist the tourism operations of Tadom Hill Resorts to provide the best facilities for visitors' satisfaction from aspects of educational experiences, entertainment experiences, esthetics experience, and escapism experience.